2018
DOI: 10.1029/2018jg004797
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Assessment of Relating Resazurin–Resorufin Experiments to Reach‐Scale Metabolism in Lowland Streams

Abstract: The reactive tracer resazurin is frequently used to investigate metabolic processes and hyporheic exchange in streams, because its transformation to resorufin is considered a function of oxygen turnover in the presence of living cells and thus of ecosystem respiration. This has been investigated and confirmed in a number of laboratory and batch studies but so far not unanimously been verified in the field. In this study we conducted 13 tracer tests with resazurin in different small, low-gradient streams typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Vegetation in the basin is primarily red alder in the valley bottom, with stands of Douglas fir of varied ages and shrubs on the hillslopes [24]. Stream discharge varied due to evapotranspiration in the basin [5,[22][23][24]95,[103][104][105][106][107][108], but contiguous surface flow along the reach was never observed (i.e., the reach was spatially intermittent for the entire study period). We monitored the maximum and minimum extent of surface water during the study, flagging the most expansive and contracted conditions within the study reach and mapping their positions with a topographic survey ( Figure 1).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Vegetation in the basin is primarily red alder in the valley bottom, with stands of Douglas fir of varied ages and shrubs on the hillslopes [24]. Stream discharge varied due to evapotranspiration in the basin [5,[22][23][24]95,[103][104][105][106][107][108], but contiguous surface flow along the reach was never observed (i.e., the reach was spatially intermittent for the entire study period). We monitored the maximum and minimum extent of surface water during the study, flagging the most expansive and contracted conditions within the study reach and mapping their positions with a topographic survey ( Figure 1).…”
Section: Site Descriptionmentioning
confidence: 99%
“…In the presence of mildly reducing conditions, Raz undergoes an irreversible reduction to its daughter product resorufin, Rru, and experimental work with microbial communities has shown that (1) the transformation of Raz to Rru is proportional to oxygen consumption (González‐Pinzón et al, 2012) and (2) the mass balance of Raz and Rru closes over time scales relevant for field experiments (Dallan et al, 2020). Therefore, the transformation from Raz to Rru has been used as a proxy for in situ aerobic metabolism and water‐sediment interactions in the last decade (Argerich et al, 2011; González‐Pinzón et al, 2014, 2016; González‐Pinzón et al, 2015b; Knapp & Cirpka, 2018; see review by Knapp et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…(2) the mass balance of Raz and Rru closes over time scales relevant for field experiments (Dallan et al, 2020). Therefore, the transformation from Raz to Rru has been used as a proxy for in situ aerobic metabolism and water-sediment interactions in the last decade (Argerich et al, 2011;González-Pinzón et al, 2014González-Pinzón et al, 2015b;Knapp & Cirpka, 2018; see review by .…”
Section: Experimental Setup and Field Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…A key problem is that the most successful studies on hyporheic exchange and the reactivity of the hyporheic zone were performed in small, comparably steep, low-order streams whereas waste-water treatment plants are typically located at somewhat larger, less steep, higher-order rivers with little hyporheic exchange. Also, the transferability of resazurin reactivity to aerobic metabolism is limited (Knapp & Cirpka, 2018). Finally, there is no experience and reasonable way to relate or transfer any such rates to the turnover rate of emerging pollutants.…”
Section: Introductionmentioning
confidence: 99%